Planning Schemes for Human Settlements in the Desert Areas - كمونة, أ.د.حيدر عبدالرزاق (Journal of Planner and Development, 2009)
Despite the vast areas occupied by deserts in the world, it is still far from the civilized development and development of the other regions, so they became semi-neglected areas that extend to the hand of urbanization only in specific places and for special purposes, due to the harsh natural conditions surrounding it and to the accuracy The ecological balance in it became the greatest enemy of human beings in the desert areas is the same person who paved the way for increased intervention in the exploitation of natural resources and increase the demand for them to drain seriously affect the impact and still on the environmental and climatic conditions and thus living for the inhabitants of these Areas. The main potential for development in the desert areas is varied and varied. It includes agriculture, tourism, wind and sun exploitation, military and scientific site features, industry and mining, and finally human settlement, which are possibilities for one and can be exploited in an exemplary and thoughtful way to serve the process of civilized progress in the world.